Factors determining the smooth flow and the non‐operative time in a one‐induction room to one‐operating room setting. Issue 2 (11th December 2014) - Mulier, Jan P.; De Boeck, Liesje; Meulders, Michel; Beliën, Jeroen; Colpaert, Jan; Sels, Annabel
Abstract: Rationale, aims and objectives: What factors determine the use of an anaesthesia preparation room and shorten non‐operative time? Methods: A logistic regression is applied to 18 751 surgery records from AZ Sint‐Jan Brugge AV, Belgium, where each operating room has its own anaesthesia preparation room. Surgeries, in which the patient's induction has already started when the preceding patient's surgery has ended, belong to a first group where the preparation room is used as an induction room. Surgeries not fulfilling this property belong to a second group. A logistic regression model tries to predict the probability that a surgery will be classified into a specific group. Non‐operative time is calculated as the time between end of the previous surgery and incision of the next surgery. A log‐linear regression of this non‐operative time is performed. Results: It was found that switches in surgeons, being a non‐elective surgery as well as the previous surgery being non‐elective, increase the probability of being classified into the second group. Only a few surgery types, anaesthesiologists and operating rooms can be found exclusively in one of the two groups. Analysis of variance demonstrates that the first group has significantly lower non‐operative times. Switches in surgeons, anaesthesiologists and longer scheduled durations of the previous surgery increases the non‐operative time. A switch in both surgeon and anaesthesiologist strengthens this negative effect. Only a few operating rooms and surgery types influence the non‐operative time. Conclusion: The use of the anaesthesia preparation room shortens the non‐operative time and is determined by several human and structural factors.